2020
DOI: 10.1093/scan/nsaa160
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma, brain structure and emotion recognition in patients with schizophrenia and healthy participants

Abstract: Childhood trauma, and in particular physical neglect, has been repeatedly associated with lower performance on measures of social cognition (e.g. emotion recognition tasks) in both psychiatric and non-clinical populations. The neural mechanisms underpinning this association have remained unclear. Here, we investigated whether volumetric changes in three stress-sensitive regions – the amygdala, hippocampus and anterior cingulate cortex (ACC) - mediate the association between childhood trauma and emotion recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 88 publications
1
20
0
Order By: Relevance
“…Our findings are consistent with previous reports highlighting the importance of environmental variables in modifying biological processes that influence variability in intelligence in both clinical 14,33,34 and nonclinical samples 35,36 . The significant moderating effect of ELA on the association between IQ-PGS, GM volume and intelligence reported here adds weight to the hypothesis that exposure to adversity contributes to detrimental biological brain changes that persist into adulthood and with lasting consequences for intellectual development.…”
Section: Environmental Exposure As a Moderator Of The Genetic And Bra...supporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with previous reports highlighting the importance of environmental variables in modifying biological processes that influence variability in intelligence in both clinical 14,33,34 and nonclinical samples 35,36 . The significant moderating effect of ELA on the association between IQ-PGS, GM volume and intelligence reported here adds weight to the hypothesis that exposure to adversity contributes to detrimental biological brain changes that persist into adulthood and with lasting consequences for intellectual development.…”
Section: Environmental Exposure As a Moderator Of The Genetic And Bra...supporting
confidence: 93%
“…In particular, many studies have reported an association between intelligence and early life adversity (ELA); that requires significant adaptation due to, for example, abuse, neglect, witnessing domestic or other violence, and chronic poverty 11,12 . In both clinical and non-clinical samples, ELA has been found to be associated with variability in brain structure, including reductions in total grey matter volume 13,14 , and across limbic and prefrontal regions [15][16][17] . However, it should be noted that most studies have not examined the extent to which genetic factors interact with the effects of ELA on brain structure and intelligence.…”
Section: Introductionmentioning
confidence: 99%
“…Research to date has also examined theory of mind, emotion recognition, and other social cognitive abilities in schizophrenia as a function of childhood trauma ( e.g. , Rokita et al, 2020, 2021; Vaskinn et al, 2020), and therefore, understanding the role of suicide among these constructs is vital.…”
Section: Discussionmentioning
confidence: 99%
“…Schizophrenia is a complex neurodevelopmental disorder that is characterized by the presence of symptoms like delusions, hallucinations, disorganized speech, and negative affect ( James et al, 2018 ; NIMH, 2020 ). While the mechanistic underpinnings of schizophrenia can be genetically derived ( He et al, 2021 ) another risk factor is early life adversity, where certain environmental stressors (e.g., physical or emotional abuse, maternal infection) contribute to permeant changes in brain physiology and behavior ( Bennouna-Greene et al, 2011 ; Kraan, et al, 2015 ; Rokita et al, 2020 ; Matheson et al, 2013 ). Stress in the prenatal environment can increase one’s risk for developing psychiatric disorders including schizophrenia.…”
Section: Schizophreniamentioning
confidence: 99%